2023
DOI: 10.3390/antiox12010113
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Antioxidant Characterization of Opuntia robusta Fruit Extract and Its Protective Effect against Diclofenac-Induced Acute Liver Injury in an In Vivo Rat Model

Abstract: A molecular characterization of the main phytochemicals and antioxidant activity of Opuntia robusta (OR) fruit extract was carried out, as well as an evaluation of its hepatoprotective effect against diclofenac (DF)-induced acute liver injury. Phenols, flavonoids and betalains were quantified, and antioxidant characterization was performed by means of the ABTS•+, DPPH and FRAP assays. The identification of the main biocompounds present in OR fruit extract was carried out via UPLC-QTOF-MS/MS. In the in vivo mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…Upon DNA damage, GADD45A is rapidly produced in the cell to participate in the DNA damage repair process, and at the same time, it induces cell cycle arrest and/or apoptosis 34 . As HIRI is often accompanied by acute and severe impairment of mitochondrial and DNA damage 35 , given which GADD45A is up-regulated and involved in pathological processes in HIRI, a small number of studies have reported on the predictive and diagnostic potential of GADD45A in drug-induced liver injury 36 , 37 . However, there are currently very few studies reporting on the exact mechanism of GADD45A involvement in HIRI.…”
Section: Discussionmentioning
confidence: 99%
“…Upon DNA damage, GADD45A is rapidly produced in the cell to participate in the DNA damage repair process, and at the same time, it induces cell cycle arrest and/or apoptosis 34 . As HIRI is often accompanied by acute and severe impairment of mitochondrial and DNA damage 35 , given which GADD45A is up-regulated and involved in pathological processes in HIRI, a small number of studies have reported on the predictive and diagnostic potential of GADD45A in drug-induced liver injury 36 , 37 . However, there are currently very few studies reporting on the exact mechanism of GADD45A involvement in HIRI.…”
Section: Discussionmentioning
confidence: 99%
“…Villa-Jaimes et al [31] evaluated immunohistochemical analyses of the livers of adult rats pretreated with an aqueous extract of Opuntia robusta fruit (800 mg/kg) and the Opuntia-derived phytochemicals betanin (25 mg/kg) and N-acetylcysteine (50 mg/kg) for 5 days before inducing acute toxicity with diclofenac on the sixth day. The results of the immunohistochemical analysis revealed a significant increase in the number of active caspase-3-positive cells in the diclofenac-treated group compared with the control group.…”
Section: Animal Model Studiesmentioning
confidence: 99%
“…A recent study reported a protective effect on liver cells against acute injury caused by Diclofenac; they stated that Opuntia robusta fruit extract displayed strong antioxidant activity linked to its cytoprotective effect [ 159 ].…”
Section: The Protective and Preventive Role Of Bioactive Compounds Ag...mentioning
confidence: 99%